THE EFFECT OF NON CASH PAYMENT SYSTEM ON CUSTOMER COMPLIANCE IN LOAN REPAYMENT AT PT. PEGADAIAN BOSWESEN BRANCH - Makalisang, Meiland; Lengkong, Viktor; Pandowo, Merinda H. Ch.; Lumintang, Genita G.; Mintardjo, Christoffel M. O. (Management Studies and Business Journal (PRODUCTIVITY), 2025)
The digitalization of financial services has driven the increased use of non-cash payment systems at various financial institutions, including PT. Pegadaian. However, customer compliance in repaying loans remains suboptimal. This study aims to analyze the effect of non-cash payment systems on customer compliance in repaying loans at PT. Pegadaian, Boswesen Branch. Using a quantitative approach with simple linear regression analysis, this study processed data collected through a structured questionnaire from gold pawn customers. The results showed that the use of non-cash payment systems did not significantly impact customer compliance. This finding indicates that compliance is more determined by factors other than the use of payment technology, such as financial awareness, understanding of payment obligations, and level of trust in the institution. This study recommends that further studies consider psychological, behavioral, and financial literacy variables to gain a more comprehensive understanding of the determinants of customer compliance.